Pharmacotherapy of Pain in the Older Population: The Place of Opioids - Prostran, Milica; Vujović, Katarina Savić; Vučković, Sonja; Medić, Branislava; Srebro, Dragana; Divac, Nevena; Stojanović, Radan; Vujović, Aleksandar; Jovanović, Lepa; Jotić, Ana; Cerovac, Nataša (Frontiers in Aging Neuroscience, 2016)
Pain is a common symptom in older people. It is possible that pain is underreported in older persons due to an incorrect belief that it is an inevitable part of aging. Opioid analgesics are potent medications, with confirmed efficacy for the treatment of moderate to severe pain. These drugs are commonly used in older persons. However, there is insufficient evidence regarding safety of opioids in older patients. One of the reasons for this is the lack of randomized, controlled clinical trials. People of advanced age often have comorbidites and use other prescription drugs, as well as over-the-counter (OTC) compounds, thus making them more suceptible to the risk of interactions with opioids. Significant pharmacokinetic and pharmacodynamic changes that occur with advancing age increase the risk of adverse effects of opioids. There are also some discrepancies between guidelines, which recommend the use of lower doses of opioids in older patients, and the findings in the literature which suggest that pain is often undertreated in this age group. It seems that there are significant variations in the tolerability of different opioid analgesics in older people. Morphine, fentanyl, oxycodone and buprenorphine are still the preferred evidence-based choices for add-on opioid therapy for these patients. However, the safety and efficacy of other opioids in older patients, especially if comorbidities and polypharmacy are present, is still questionable. This review addresses the most important aspects of the use of opioids in older persons, focusing on pharmacokinetics, pharmacodynamics, adverse effects and interactions.